1997
DOI: 10.1111/j.1525-1594.1997.tb00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulocytapheresis in the Treatment of Patients with Rheumatoid Arthritis

Abstract: The G-1 column is an extracorporeal type granulocytapheresis device packed with 220 g cellulose acetate beads to which granulocytes and monocytes specifically adhere. A total of 59 rheumatoid arthritis patients with elevated granulocyte counts from 4 hospitals in Japan received 2 apheresis sessions of 1 h duratiodweek for a total of 8 times over a period of 4 weeks. About 55% of the leukocytes which entered the G-1 column were adsorbed onto the beads; 95% were granulocytes, 3.5% monocytes, and 0.4% lymphocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(29 citation statements)
references
References 24 publications
(19 reference statements)
0
28
0
1
Order By: Relevance
“…As indicated above, the Adacolumn carriers remove from the blood in the column about 65% of granulocytes (mostly neutrophils), 55% of monocytes, and a very small fraction of lymphocytes [1][2][3]. These are the leukocytes which bear the so-called Fcγ R and complement receptors [1,18].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As indicated above, the Adacolumn carriers remove from the blood in the column about 65% of granulocytes (mostly neutrophils), 55% of monocytes, and a very small fraction of lymphocytes [1][2][3]. These are the leukocytes which bear the so-called Fcγ R and complement receptors [1,18].…”
Section: Discussionmentioning
confidence: 97%
“…The device utilizes cellulose acetate (CA) beads as the column adsorptive leukocytapheresis carriers for selective depletion of GMs from peripheral blood. Pre and post column leukocyte counts have revealed that the carriers adsorbs about 65% of granulocytes, 55% of monocytes/macrophages, and a small fraction of lymphocytes from the blood in the column [3]. While GM adsorption has been regarded as the main mechanism for clinical efficacy in treated patients, there are views [1,2] that the depletion of GMs per se does not fully account for the observed clinical efficacy.…”
mentioning
confidence: 98%
“…More specifi cally, the G-1 beads adsorb up to 67% of granulocytes, 55% of monocytes, and about 2% of lymphocytes from the blood in the column. 32 Several studies have reported that GMA reduces the magnitude of secretion of infl ammatory cytokines by peripheral blood leukocytes. 31,[33][34][35][36][37][38][39][40] However, the clinical effi cacy of GMA cannot be fully explained by the reduction in numbers activated leukocytes itself.…”
Section: Introductionmentioning
confidence: 99%
“…A novel adsorptive-type granulocyte and monocyte (GM) apheresis (GMA) device (Adacolumn) can deplete excess and activated GMs from the peripheral blood of patients with inflammatory diseases including RA [5] and UC [6,7]. The device comprises a column filled with 2-mm cellulose acetate (CA) beads that act as carriers for adsorptive leukocyte apheresis [8].…”
mentioning
confidence: 99%